Mitochondrial Dysfunction and Its Role in Disease Pathogenesis (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article defines that  mitochondria are essential organelles responsible for cellular energy production through oxidative phosphorylation. Mitochondrial dysfunction plays a significant role in apoptosis, necrosis, and oxidative stress, influencing disease progression in conditions like Parkinson’s disease, Alzheimer’s disease, and multiple sclerosis. Inherited through maternal transmission or nuclear mutations, mitochondrial disorders exhibit complex inheritance patterns, with heteroplasmy and threshold effects impacting disease expression. Advances in genetic research and metabolic studies have improved understanding, but effective treatments remain limited. Future therapeutic strategies, including targeted gene therapy and metabolic interventions, hold promise for managing mitochondrial diseases and mitigating their systemic effects.